Поведінка підприємств щодо розв'язання проблеми взаємодії попиту і пропозиції - Лінькова, Олена Юріївна (SWorld & D.A. Tsenov Academy of Economics, 2021)
Аналіз досвіду врегулювання попиту та пропозиції за часів пандемії COVID-19 є основою запропонованого напрямку організаційного розвитку через управління організаційними проектами в полі обраної бізнес-моделі. Врахування ціннісних орієнтацій в проектному підході дозволили сформувати компенсатори його високого динамізму при практичному застосуванні: системне навчання та опрацювання нових топових професійних навичок; формування мікроклімату взаємодопомоги в командах; своєчасне інформування персоналу про зміни ринкових факторів, які впливають на запровадження організаційних змін; підвищена матеріальна підтримка на рівні стратегічного менеджменту індивідуальної роботи менеджерів операційного рівня.

Analysis of the experience of supply and demand settlement during the COVID-19 pandemic is the basis of the proposed direction of organizational development through the management of organizational projects in the field of the selected business model. Taking into account the value orientations in the project approach allowed to form compensators of its high dynamism in practical application: systematic training and development of new top professional skills; formation of a microclimate of mutual assistance in teams; timely informing staff about changes in market factors that affect the implementation of organizational change; increased material support at the level of strategic management of individual work of operational level managers. Current management measures: introduction of staff training programs; monitoring of supply and demand in the market; improving the skills of managers to organize work; introduction of appropriate communication technologies; introduction of integrated management systems; updating of strategic, information and logistics subsystems. During the COVID-19 pandemic, management encountered objective problems: features of remote work (remote office work); consumer retention subject to certain restrictions on movement, both in the country and abroad; change of consumer priorities; reduction of purchasing power (increase in poverty); growth of transport costs.
Behavior of enterprises regarding the solution of the problem of interaction of demand and supply
Keywords: споживчі пріорітети; управління змінами; бізнес-моделі; навички менеджерів; навчання персоналу; consumer priorities; change management; business models; managerial skills; staff training